2016
DOI: 10.3390/su8090939
|View full text |Cite
|
Sign up to set email alerts
|

Extended FMEA for Sustainable Manufacturing: An Empirical Study in the Non-Woven Fabrics Industry

Abstract: Abstract:Failure modes and effects analysis (FMEA) substantially facilitates the efforts of industrial manufacturers in prioritizing failures that require corrective actions to continuously improve product quality. However, the conventional approach fails to provide satisfactory explanation of the aggregate effects of a failure from different perspectives such as technical severity, economic severity, and production capacity in some practical applications. To fulfill the existing gap in the FMEA literature, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 56 publications
(62 reference statements)
0
21
0
2
Order By: Relevance
“…To fulfill this gap, Nguyen et al [25] proposed an extension by considering the associated quality costs and the capability of a failure detection system as additional determinants to signify the priority level for each failure mode. Analytical results indicated that the proposed approach remarkably reduced the percentage of defective fabrics, thus significantly reducing wastes and increasing the operational efficiency.…”
Section: Competitive and Sustainable Manufacturing Approachesmentioning
confidence: 99%
“…To fulfill this gap, Nguyen et al [25] proposed an extension by considering the associated quality costs and the capability of a failure detection system as additional determinants to signify the priority level for each failure mode. Analytical results indicated that the proposed approach remarkably reduced the percentage of defective fabrics, thus significantly reducing wastes and increasing the operational efficiency.…”
Section: Competitive and Sustainable Manufacturing Approachesmentioning
confidence: 99%
“…Detection absolutely certain to detect --------> no control exists Source: (Nguyen et al, 2016) The calculation procedures of DEMATEL can be summarized into the following steps (Tsai et al, 2017;Chen et al, 2016;Deng et al, 2014;Luthra et al, 2016;):…”
Section: No Aspect 1 Rating Values --------> 10mentioning
confidence: 99%
“…Step 2.6: Based on Equations (16)- (18), the elements of failure modes that need to be modified are determined to be: AES = {(2,1,1), (2,1,3), (2,4,1), (2,4,2), (2,4,3), (2,5,1), (2,5,2), (2,5,3), (2,6,3), (2,7,2), (2,8,1), (2,8,2), (2,8,3), (3,2,2), (3,2,3), (3,3,1), (3,3,2), (3,4,1), (3,4,2), (3,4,3), (3,6,1), (3,6,2), (3,7,1), (3,7,2), (3,7,3), (3,8,2), (3,9,1), (3,9,2)}.…”
Section: Failure Modes Severity(s) Occurrence(o) Detection(d)mentioning
confidence: 99%
“…As a formal system analysis approach, the technique of FMEA was originally proposed in the 1960s, and was intended to satisfy the aerospace industry's apparent safety and reliability requirements [4]. Since then, the FMEA method has been successfully used in various industries as a simple and powerful tool to enhance the safety and reliability of products, systems, and processes in industry, such as the aerospace [5], energy [6], heath care and hospital [7], and manufacturing industries [8].…”
Section: Introductionmentioning
confidence: 99%